Indigenous knowledge of wild plants collected in Darfur, Sudan. - Hegazy, Ahmad K; Hosni, Hasnaa A; Lovett-Doust, Lesley; Kabiel, Hanan F; Badawi, El-Shafei; Mwavu, Edward N (Ethnobotany Research and Applications, 2020)
Background: The lives of the “Fur”, indigenous people of Darfur, Sudan are intimately connected to local wild plants, but the traditional uses of these plants are, so far, poorly documented. Many species are indigenous to the region, but others are introduced, and have naturalized over millennia. Methods: For a month each summer from 2014-2016, using questionnaire interviews, direct observation of practices, and a literature review, 58 species were identified. An “importance value” for each was determined, based on the intensity and season(s) of use, in eight use categories. For each species, a “concordance ratio” characterized the degree of agreement between indigenous knowledge and our current “scientific understanding” of their value. Results: All species were multi-use; animal forage, “other functional uses”, traditional medicine, and construction predominated. Some species are declining due to overharvesting by the growing local population, exacerbated by conflict and refugee encampments. Most of the species are used in traditional medicines, but active ingredients have been scientifically confirmed for only half of them. Surprisingly, several species with known medicinal ingredients are not used locally. Conclusions: The “Fur” people have long combined agriculture with pastoralism and wildcrafting. For this to be sustainable, it is critical to understand cultural contexts and recognize multi-use species. This can help identify new medicines, and guide sustainable development of local resources, adapted to local conditions. Naturalized wild fruit trees may have evolved drought resistance in this increasingly dry savanna climate; such genes might usefully be incorporated in crop strains elsewhere as climate change proceeds. Key words: Ethnobotany, Multipurpose-Use Plants, Importance Value, Indigenous Knowledge Index, Scientific Knowledge Index, Concordance Value, Plant Diversity, Climate Change